Investigation of Intestinal Microbes of Five Zokor Species Based on 16S rRNA Sequences - Yao Zou; Quan Zou; Hui Yang; Chongxuan Han (Microorganisms)
Zokor is a group of subterranean rodents that are adapted to underground life and feed on plant roots. Here, we investigated the intestinal microbes of five zokor species (Eospalax cansus, Eospalax rothschildi, Eospalax smithi, Myospalax aspalax, and Myospalax psilurus) using 16S amplicon technology combined with bioinformatics. Microbial composition analysis showed similar intestinal microbes but different proportions among five zokor species, and their dominant bacteria corresponded to those of herbivores. To visualize the relationships among samples, PCoA and PERMANOVA tests showed that the intestinal microbes of zokors are largely clustered by host species, but less so by genetics and geographical location. To find microbes that differ among species, LefSe analysis identified Lactobacillus, Muribaculaceae, Lachnospiraceae_NK4A136_group, unclassified_f_Christensenellaceae, and Desulfovibrio as biomarkers for E. cansus, E. rothschildi, E. smithi, M. aspalax, and M. psilurus, respectively. PICRUSt metagenome predictions revealed enriched microbial genes for carbohydrate and amino acid metabolism in E. cansus and E. smithi, and for cofactor and vitamin metabolism as well as glycan biosynthesis and metabolism in E. rothschildi, M. aspalax, and M. psilurus. Our results demonstrated differences in the microbial composition and functions among five zokor species, potentially related to host genetics, and host ecology including dietary habits and habitat environment. These works would provide new insight into understanding how subterranean zokors adapt to their habitats by regulating intestinal microbes.